Analysis of Interaction between Flame Torch and Independent Cocurrent Flow - M.A. Belotserkovsky (National Academy of Sciences of Belarus, State Scientific Institution “The Joint Institute of Mechanical Engineering", 2013)
The paper presents a theoretical analysis of the flame spraying with an independent source of cocurrent flow. The spraying process is represented by "three-layer model", describing the motion of a two-phase jet in cocurrent flow. For the numerical simulation of two-phase turbulent flows used k-ε turbulence model by Londer-Jones. To determine the required velocity of the particles in the flame were calculated necessary velocities of cocurrent flow.